2018
DOI: 10.3390/ijerph15040636
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Personality in Suicidal Ideation from the Perspective of the Interpersonal-Psychological Theory of Suicide

Abstract: The Interpersonal-Psychological Theory of Suicide (IPTS) has been increasingly studied over the last years, responding to the demand for a valid framework addressing suicidality. Yet, only a few studies have explored the function of personality in the IPTS and none with clinical patients. We aimed to contribute to fill this gap in investigating the relationship between personality as conceptualized by the Five-Factor Model, the IPTS constructs, and a dimensional measure of current suicidal ideation. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…Data on the attitudes and reactions of individuals following attempted suicide are limited. However, the initial recovery of aspects after an attempted suicide has been reported to be related to at least two demoralization subconstructs, namely hopelessness and the loss of meaning in life [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Data on the attitudes and reactions of individuals following attempted suicide are limited. However, the initial recovery of aspects after an attempted suicide has been reported to be related to at least two demoralization subconstructs, namely hopelessness and the loss of meaning in life [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…P a r t i c i p a n t s a n s w e r e d i n q u i r i e s r e g a r d i n g t h e i r sociodemographic situations as well as a series of questionnaires, some administered by the psychiatrist in charge of the study inclusion and some self-reported. Other aspects of this global project on suicide, not relevant to the present study, have resulted in five publications (28)(29)(30)(31)(32). This study was approved by the local Research Ethics Committee under the registration number 14-168.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction between PB and TB was significantly associated with suicidal ideation, whereas the interaction between PB, TB, and acquired capability for suicide was significantly associated with a greater number of prior suicide attempts (Chu et al, ). Nonetheless, while the IPTS may explain the transition from suicidal ideation to lethal suicide attempt, it does not explicitly account for factors that may influence the development of suicidality such as substance misuse, depression, self‐esteem, personality traits, and childhood abuse (Baertschi, Costanza, Canuto, & Weber, ; Roy, ; Silva, Ribeiro, & Joiner, ; Taylor, Dhingra, Dickson, & McDermott, ).…”
mentioning
confidence: 99%